2017
DOI: 10.1007/s11104-017-3521-5
|View full text |Cite
|
Sign up to set email alerts
|

Soil characteristics determine the rhizobia in association with different species of Mimosa in central Brazil

Abstract: Background and aims To evaluate the influence of soil type on the symbiosis between Mimosa spp. and rhizobia. Methods A greenhouse experiment was carried out with trap plants using seeds of six species of Mimosa and soils from three different locations in central Brazil: Posse, Brasília and Cavalcante. Plant dry biomass and number of nodules were measured after four months. Symbiotic bacteria were isolated from nodules and their molecular identification was performed. Three housekeeping genes (16S rRNA, recA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 59 publications
4
35
0
Order By: Relevance
“…Although European, African and American species of Lupinus are generally considered to be nodulated by slowgrowing rhizobia affiliated to different Bradyrhizobium lineages (see Andrews and Andrews 2017 The ability of Microvirga to nodulate lupines may be related to the soil physicochemical properties where they grow. It is known that biotic, for example, the composition and diversity of the microbial community, and abiotic factors, such as salinity, pH, altitude, nutrient availability, etc., play an important role in the interactions between the two partners (Thrall et al 2011;Lemaire et al 2015Lemaire et al , 2016Wang et al 2017;de Castro-Pires et al 2018). The Microvirga LUP strains were isolated form L. cosentinii grown in alkaline soils (pH 7Á5) of the Maamora forest, which is in line with previous results on Microvirga strains recovered from L. micranthus and L. luteus growing in Tunisian alkalinized soils (Msaddak et al 2017a(Msaddak et al , 2017bRejili et al 2019) and suggests that the soil pH is a key factor for determination of the biogeography of the Microvirga species.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Although European, African and American species of Lupinus are generally considered to be nodulated by slowgrowing rhizobia affiliated to different Bradyrhizobium lineages (see Andrews and Andrews 2017 The ability of Microvirga to nodulate lupines may be related to the soil physicochemical properties where they grow. It is known that biotic, for example, the composition and diversity of the microbial community, and abiotic factors, such as salinity, pH, altitude, nutrient availability, etc., play an important role in the interactions between the two partners (Thrall et al 2011;Lemaire et al 2015Lemaire et al , 2016Wang et al 2017;de Castro-Pires et al 2018). The Microvirga LUP strains were isolated form L. cosentinii grown in alkaline soils (pH 7Á5) of the Maamora forest, which is in line with previous results on Microvirga strains recovered from L. micranthus and L. luteus growing in Tunisian alkalinized soils (Msaddak et al 2017a(Msaddak et al , 2017bRejili et al 2019) and suggests that the soil pH is a key factor for determination of the biogeography of the Microvirga species.…”
Section: Discussionsupporting
confidence: 88%
“…; de Castro‐Pires et al . ). The Microvirga LUP strains were isolated form L. cosentinii grown in alkaline soils (pH 7·5) of the Maamora forest, which is in line with previous results on Microvirga strains recovered from L. micranthus and L. luteus growing in Tunisian alkalinized soils (Msaddak et al .…”
Section: Discussionmentioning
confidence: 97%
“…In addition, Naamala et al observed that species of Bradyrhizobium were the major rhizobia detected in G. max [23]. Undoubtedly, fewer rhizobia were characterized in our study, which we speculate could be attributable to the influence of saline soil [24]. This assumption tends to be supported by the result of a previous study that reported rhizobial distribution was affected by environment and soil characteristics [22].…”
Section: Discussionsupporting
confidence: 80%
“…In addition to cowpea, Mimosa spp. rhizobia are also influenced by soil conditions in Brazil (Pires et al 2018;de Oliveira et al 2019).…”
Section: Discussionmentioning
confidence: 99%